Pertumbuhan Artemisia vulgaris Secara Kultur Pucuk pada Medium dengan Kandungan Mioinositol dan Ekstrak Khamir - Sri Kasmiyati; Maria M. Herawati; Elizabeth B.E. Kristiani (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The effects of mioinositol and yeast extract were studied to assess their influence on growth of plantlets of Artemisia vulgaris by shoot culture. The plants regeneration of A. vulgaris were established by removing the nodes of stem and growing in MS multiplication medium with 1 ppm kinetin and 1 ppm NAA for 4 weeks. Shoots were induced for roots on MS treatment medium supplemented with mioinositol and yeast extract, added with 2 ppm IBA. Combination of four levels mioinositol concentration (mg/l): 100, 200, 300, and 400, and four levels of yeast extract concentration (mg/l): 0, 200, 300, and 400 were simultaneously added. Plantlets (2 weeks) were sub cultured on semi liquid MS medium. Plantlets were harvested on 6 weeks old. Measured parameters were fresh weight of plantlets. Data were analyzed using ANOVA followed by HSD test (p=95%). The results showed that the treatment of mioinositol and yeast extract were not significantly influenced on fresh weight of plantlets. Yeast extract was not influenced the growth of plantlets. The growth and morphogenesis of plantlets A. vulgaris were induced in treatment 100 ppm mioinositol, and addition mioinositol were higher than 100 ppm not significantly influenced the growth of plantlets.